Characteristic of Soil Chemistry Under A Few Kind of Tree in Sub Watershed Petani of Deli Serdang District - yudiansyah pane (Universitas Sumatera Utara, 2016)
This research to know about soil chemical characteristic under some vegetation on the sub Watershed of Petani in Buluh Awar Village Sibolangit Sub Dictricts and Deli Serdang Districts have been done on march to october 2015. The soil samples were analyzed at Laboratory of Soil Research, Bogor and Socfindo Laboratory, Medan, North Sumatera. This research used descriptive method with purposive sampling method. The data was analyzed by T test of 5% level. The results showed that the parameters of C-organic , total N, P-available, K-exchangeable, CEC have changes decrease soil chemical properties under the Sugar palm vegetation, durian and rubber are significant to the soil under forest, the highest decrease in chemical properties located on land under rubber with the average value of soil organic C 1.10% and the average value of exchange amounted to 0.166 K- cmol / kg. And on the Vegetation durian have the lowest decrease changes. Keywords: Durian, Forest, Rubber, Soil chemistry, Sugar palm,